2000
DOI: 10.1038/sj.ejcn.1600906
|View full text |Cite
|
Sign up to set email alerts
|

Association between trans fatty acid intake and cardiovascular risk factors in Europe: the TRANSFAIR study

Abstract: Background: High intakes of trans fatty acids (TFA) have been found to exert an undesirable effect on serum lipid pro®les, and thus may increase the risk for cardiovascular disease. Objective: Investigation of the association between TFA intake and serum lipids. Design: Cross-sectional study in eight European countries (Finland, France, Greece, Iceland, The Netherlands, Portugal, Spain, Sweden) among 327 men and 299 women (50 ± 65 y). Using a dietary history method, food consumption was assessed and TFA intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 32 publications
(41 reference statements)
4
51
0
3
Order By: Relevance
“…13 This is similar to estimates for Western Europe (0.9-1.0% of E, 2.0-2.4 g day À1 ) 34 and Australasia (0.5-0.6% of E, 1.2-1.6 g day À1 ), 35 but higher levels have been reported for Canada (2.2% of E, 4.9 g day À1 ) 36 and the United States (1.8-2.2 g day À1 ). 37 The details of all human studies are summarized in Table 2 (Epidemiological) and Table 3 (Meal studies).…”
Section: Human Studiessupporting
confidence: 77%
“…13 This is similar to estimates for Western Europe (0.9-1.0% of E, 2.0-2.4 g day À1 ) 34 and Australasia (0.5-0.6% of E, 1.2-1.6 g day À1 ), 35 but higher levels have been reported for Canada (2.2% of E, 4.9 g day À1 ) 36 and the United States (1.8-2.2 g day À1 ). 37 The details of all human studies are summarized in Table 2 (Epidemiological) and Table 3 (Meal studies).…”
Section: Human Studiessupporting
confidence: 77%
“…The SFA content rose steadily from the 5 -8% values of the 1960s in Crete and Corfu to the 15% of Crete adolescents recorded some 20 -30 y later , and to the remarkably high values of 19 and 20% energy in Athens (Katsouyanni et al, 1991;Trichopoulou et al, 1993). It should be noted, however, that at least in one case, when the SFA content was assessed by chemical analysis (van de Vijver et al, 2000), the directly assessed value was 9.5 and 10.8%, ie considerably lower and only marginally above the internationally agreed 10% goal.…”
Section: The Evolution Of the Greek Dietmentioning
confidence: 89%
“…On the whole, all these recently available data suggest that the current fat intake in Greece is very high, ranging from a minimum average of 35% (van de Vijver et al, 2000) to a maximum of 47% (Katsouyanni et al, 1991). Given these group averages and assuming a hypothetical but realistic standard deviation for fat intake of 10%, a substantial proportion of Greeks may now be consuming a diet whose fat content exceeds 50%.…”
Section: The Evolution Of the Greek Dietmentioning
confidence: 99%
“…20 In addition, the multicentric Transfair study concluded that trans fatty acids are not associated with an unfavourable serum lipid profile at the current European intake levels. 21 Conformational studies suggest that trans-monounsaturated fatty acids are viewed as SFA in the cell and thus display the biological behaviour of a saturated fatty acid (they are incorporated in a phospholipid structure in place of a saturated fatty acid). This is partly explained by steric features showing large similarities between trans-monounsaturated fatty acids and unsaturated fatty acids and between trans-PUFA and monounsaturated fatty acids (Figure 3).…”
Section: Hypertension Monounsaturated and Trans Fatty Acidsmentioning
confidence: 99%